Hide Secret Script Encryption in Video Frames Based on Magic Square - Al-Dabbas, Maisaa (Al-Qadisiyah Journal of Pure Science, 2021)
This article hides mystery texts in vidiums using cipher mystery message in vidiums, the objective that work is conceal big datum in frame of video. The fast of increase in rising speed communication nets technologies and make to forward of datum is simple. Thus, it can be suggested modern manner for conceal mystery texts that big size into frame of vidium efficiently, powerful and height capacity. This system depends on of three main steps: the first step: partition texts and ciphering, the second step: partition vidium to a collection of frames, and the final step: hide mystery texts in frame of vidium uses mystery key is magic square. The outcomes of system are excellent in conceal big text without sensible by attacker, through utilized the evaluation of system in each vidium frame in "PSNR, MSE, Entropy, Histogram, and correlation coefficient".